AIDS survival and progression in black Africans living in south London, 1986-1994. Issue 1 (February 1996) - Low, N; Paine, K; Clark, R; Mahalingam, M; Pozniak, A L
Abstract : OBJECTIVES: To describe the rate of progression to AIDS and survival following AIDS diagnosis in HIV-infected Africans living in London. To identify factors influencing progression and outcome of disease. DESIGN: Retrospectively constructed prevalent cohort. SETTING: Outpatient clinic population, London. SUBJECTS: HIV-infected individuals of African origin presenting between January 1986 and October 1994. MAIN OUTCOME MEASURES: AIDS indicator illness; cumulative survival probabilities to AIDS diagnosis and from AIDS diagnosis to death; rate of progression to AIDS. RESULTS: Ninety six patients (57 women) provided 166 person years of follow up. Median CD4 lymphocyte count at presentation was 205 (90% range 20-577) x 10(6)/l. Kaplan-Meier estimates of the proportion (95% confidence interval) of patients developing AIDS from the time of enrollment were 18 (9 to 27)% at 12 months and 44 (30 to 58)% at 36 months. Only CD4 count at HIV diagnosis was independently associated with a faster rate of progression to AIDS (adjusted relative hazard 9.18%, 95% confidence interval 2.84 to 29.67, p < 0.001). The proportion (95% confidence interval) surviving following AIDS diagnosis was estimated to be 73 (55 to 91)% at 12 months and 25 (0 to 52)% at 36 months. CONCLUSIONS: HIV-infected people of sub-Saharan African origin living in London present with advanced disease. When compared with published studies, their survival experience is comparable to that observed in HIV-infected individuals born in developed countries.